2020
DOI: 10.1097/brs.0000000000003508
|View full text |Cite
|
Sign up to set email alerts
|

The Top 100 Spine Surgery Articles on Social Media

Abstract: Study Design. Literature review. Objective. To discern which social media outlets contribute most to spine surgery literature dissemination and to investigate how popular articles compare to articles with most citations. Summary of Background Data. Scientific literature is increasingly disseminated through social media. The Altmetric Attention Score (AAS) is defined as an automated, weighted score calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Twitter, newsfeeds, and Facebook are the main contributors to the Altmetric. Attention Score was not significantly correlated with the impact factor 26 .…”
Section: Introductionmentioning
confidence: 69%
“…Twitter, newsfeeds, and Facebook are the main contributors to the Altmetric. Attention Score was not significantly correlated with the impact factor 26 .…”
Section: Introductionmentioning
confidence: 69%
“…It is not surprising that researchers are also increasingly using social media to promote their research, report their findings, and collaborate with colleagues. Considering the limitations of traditional scientometric measures, alternative metrics have been introduced as complementary measures of the publication impact [ 66 ]. A growing number of researchers are cognizant of the alternative metrics, and the frequency of published articles with an Altmetric score is rapidly increasing [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the mean AAS was 63.4 ± 164.8, and the median AAS was 10.5. Previous studies in other orthopedic specialties have found a median AAS of 4 to 235, depending on the topic and age of the publication [ 66 , [68] , [69] , [70] , [71] ]. In line with other authors, we found a significant but weak correlation between the citation number and AAS across the included papers [ [3] , [67] , [68] , [69] , [72] , [73] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This showcases the degree of social media use in the medical community [11]. Previous studies have assessed the utility of new bibliometrics (ie, AASs and PlumX scores) as complements to citation count in various medical fields, but these studies have reported variable results [4,9,10,12,13]. Furthermore, the utility of altmetrics in COVID-19 research has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 98%